Local Wisdom on Town Square of Ponorogo - Sari, Wahyuni Eka (University of Merdeka Malang, 2019)
The town square that we know is open space for the public. The square is often found in almost all cities in Indonesia. The square is a part of the city that can be used as a city park. The town square in Ponorogo Regency is a square that functions as a public open space that is visited by many Ponorogo residents themselves and from outside Ponorogo. Many activities are carried out in the square. Activities such as selling, gathering, mutual interaction between individuals, exercise are carried out every day. In addition, cultural activities or official government activities are also carried out in this square. Ponorogo Square can be a unifier for Ponorogo residents themselves. The purpose of this study was to find out how the local wisdom of the Ponorogo Regency square that currently exists. The method used is descriptive analysis method using exposure from the results of field surveys. The results of this study are in the form of local wisdom conditions formed from the Ponorogo Regency square.Â DOI: https://doi.org/10.26905/lw.v11i1.2713